2015
DOI: 10.1111/ced.12695
|View full text |Cite
|
Sign up to set email alerts
|

Altered circulating endothelial progenitor cells in patients with keloid

Abstract: Evidence has suggested that vascular endothelial growth factor (VEGF), a crucial growth factor in regulating endothelial progenitor cells (EPCs), plays a central role in keloid formation. However, the levels of circulating EPCs in patients with keloid have not yet been explored. The aim of this study was to determine the number of circulating EPCs in patients with keloid. Circulating EPCs (defined as CD45- CD34+CD133+VEGFR2+cells) and VEGF levels from 39 patients with keloid and 22 healthy controls (HCs) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…The latter assumption could be dismissed as the results of CFU assay demonstrated equal numbers of primitive, definitive, and total EPC‐CFU in CD34 + cultures derived from keloid patients and healthy donors. In support of our findings, an increased number of circulating EPCs in keloid patients were identified as CD34 + CD133 + VEGFR2 + cells and were quantitated using flow cytometry by Zhang et al . Comparison of the yield of CD34 + cells isolated from peripheral blood samples of keloid patients and healthy donors revealed an almost twofold increase in circulating CD34 + cells in keloid patients, although this result was not significant.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The latter assumption could be dismissed as the results of CFU assay demonstrated equal numbers of primitive, definitive, and total EPC‐CFU in CD34 + cultures derived from keloid patients and healthy donors. In support of our findings, an increased number of circulating EPCs in keloid patients were identified as CD34 + CD133 + VEGFR2 + cells and were quantitated using flow cytometry by Zhang et al . Comparison of the yield of CD34 + cells isolated from peripheral blood samples of keloid patients and healthy donors revealed an almost twofold increase in circulating CD34 + cells in keloid patients, although this result was not significant.…”
Section: Discussionsupporting
confidence: 83%
“…The source of VEGF in keloids remains unknown. In the above cited investigation of circulating EPC in keloid patients, the levels of VEGF in patients’ blood were high, but the correlation between the number of circulating EPCs and VEGF levels was not established . One study demonstrated VEGF synthesis by keloid fibroblasts cultured in vitro .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies show that keloid patients have abnormally high VEGF levels in their plasma: Zhang et al showed that the mean ELISAdetermined VEGF levels in keloid patients were 112.0 pg/mL, vs 56.48 pg/mL in the plasma of healthy controls (P < .001). 11 Mogili et al also showed this difference (90 vs 68.9 pg/mL, P < .05). In addition, they found that keloid tissue expressed significantly more VEGF on western blot than skin from healthy controls (P = .0022), which suggests that circulating VEGF levels mimic VEGF levels in the tissue.…”
Section: Factorsmentioning
confidence: 80%
“…Keloid formation is one of the frustrating clinical problems that has been ascribed to altered growth factor regulation, aberrant collagen turnover, genetics, immune dysfunction, sebum reaction, altered circulating endothelial progenitor cells, epithelial–mesenchymal transition, and endothelial–mesenchymal transition . Numerous treatment methods have been proposed for earlobe keloids, suggesting that no single method has surfaced as the accepted standard …”
Section: Discussionmentioning
confidence: 99%